Surgical Techniques in Congenital Diaphragmatic Hernia - Morini, Francesco; Bagolan, Pietro (European Journal of Pediatric Surgery, 2012)
In congenital diaphragmatic hernia (CDH), surgery is considered the less controversial part of the treatment. However, surgical strategies for CDH are widely disparate and several surgical aspects are still being discussed. The aim of this review is to describe the current surgical treatment of CDH, examining its most controversial issues.
Keywords: congenital diaphragmatic hernia; neonates; surgical techniques